Intellectual Property Rights as Bank Credit Guarantee - Rudolf Valentino Saragih; Wiwik Sri Widiarty (Universitas Dharma Wacana, 2022)
The development of banking is increasing rapidly, especially for creative economy actors based on Intellectual Property Rights that can be used as credit guarantees or bank financing. So that there is legal certainty, the government issues regulations, namely through Government Regulation Number 24 of 2022 concerning Implementing Regulations of Law Number 24 of 2019 About the Creative Economy. This research uses normative legal analysis, which is library research that examines document studies, using secondary data such as laws and regulations, namely Law Number 28 of 2014 concerning Copyright, by using qualitative analysis. This study concludes that the regulation of Intellectual Property Rights can be used as collateral for debt credit/financing to banks through Government Regulations, namely the creative economy based on intellectual property, facilities for developing a marketing system for innovative economy products based on intellectual property, such as licenses, franchises, technology transfer, brands, jointly, transfer of rights, and other forms of partnership. The application of intellectual property rights regulations as objects of bank credit guarantees has been studied by the Financial Services Authority (OJK) because they need government support to prepare and form institutions for registration.Â